Digital storytelling in speaking skill - Moscoso Rosero, Olga Vanessa (2023)
Digital Storytelling is an innovative strategy to help students improve their English language skills. The objective of this research was to strengthen oral skills through digital storytelling in sixth grade students at the Kyryos School to achieve the objective, the digital storytelling strategy was applied through a practical action research method. The lesson planning was based on the ADDIE (Analyze, Design, Develop, Implement and Evaluate) model. The study took place over eight weeks with twenty-five students as participants. The initial phase consisted of applying a pretest to identify the level of oral skills of the students. Then, the intervention was carried out and the post test was applied to identify improvements. For the reflection process, some instruments were used: the teacher's agenda, the peer observation table, and the student survey. Subsequently, the information obtained from the instruments was analyzed using the triangulation technique.